Absolute Phase Estimation in Repeat-Pass CSAR Interferometry Based on Backprojection and Split-Bandwidth Techniques - Jianpeng Li; Daoxiang An; Yongping Song; Junyi Xu; Dong Feng; Leping Chen; Zhimin Zhou (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing, 2024)
The generation of high-precision ground digital elevation models (DEMs) based on synthetic aperture radar interferometry (InSAR) technology has attracted wide attention. Compared with the linear InSAR technique, the 360 $^°$ aperture gives circular InSAR (In-CSAR) the capability to generate a full-angle DEM of the observed region. The backprojection (BP) algorithm is considered as a preferred candidate for In-CSAR imaging since it does not impose any restrictions on flight trajectories. After phase unwrapping, a global unknown phase ambiguity exists in the unwrapped phase. Up to now, high-efficient frequency-domain methods, such as the split-bandwidth technique, have commonly been used to estimate the phase ambiguity. However, the split-bandwidth technique cannot be effectively integrated with the BP-focusing image due to the highly nonlinear and nonparallel trajectories of the airborne In-CSAR platforms. We present, for the first time, the combination of BP and split-bandwidth techniques for absolute phase estimation of In-CSAR interferogram in this article. The proposed method can avoid the phase offset induced by split-bandwidth processing under the conditions of highly nonlinear and nonparallel platform trajectories. In addition, the spectral characteristics of the BP-focusing subimage are derived in detail to correct its 2-D space-variant spectral support. In order to reduce the impact of coherence, the weighted least square is adopted to estimate unknown phase ambiguity. The processing results of simulation and real data verify that the proposed approach can effectively estimate the phase ambiguity even under the conditions of highly nonlinear and nonparallel platform trajectories.